DAMPAK PROGRAM GERAKAN TURUN KE SAWAH (GERUNWAH) TERHADAP PENINGKATAN PRODUKSI DAN KESEJAHTERAAN PETANI DI KELURAHAN DUSUN BARU KECAMATAN TABIR KABUPATEN MERANGIN - Mulyani Mulyani; Wiwin Alawiyah (Universitas Batangahari Jambi, 2018)
Food security is a national problem that needs to be immediately solved. Various policies have been done by the government in the form of efforts to increase the production of food crops including rice. One of these programs is back to rice field in the form of new or old rice fields by providing seeds, fertilizers and medicines and equipment supporting rice production. Therefore, it is necessary to conduct an in-depth study to assess whether the program's form impacts or not to farmers. Both in terms of production and welfare aspects of rice farmers. The expected output from this study is the descriptions of the impact of the government's downward movement to rice fields on farmers from both production and welfare aspects. This research was conducted in Merangin District focused on Wetland paddy farmers who follow the activities of the movement down to the rice fields that proclaimed local government. The scope of this research is focused on analyzing the impact of local government policy programs in the form of down to rice field movements to see if there is any influence on the rice farmers' production raise and the welfare of rice paddy farmers in the region. This research will be conducted from February to May 2018. The research method used is descriptive analysis research method, mean difference analysis (mean test). The data used is in the form of primary data and secondary data that is data before and after the implementation of the movement program down into the fields. The research is conducted through survey method to the place of execution of the activity. The method used for sampling in this study is simple random sampling. The result shown that program (GERUNWAH) give significant effect to increase paddy production.